Analisis Pemanfaatan Alat Permainan Tradisional untuk Pengembangan Projek Penguatan Profil Pelajar Pancasila - Herna Hastuti, Herna Hastuti; Mulyanto, Mulyanto (Universitas Sarjanawiyata Tamansiswa, 2024)
The research objectives were as follows ;(1) To nalyzing the planning, the implementation, evaluation and To analyzing the results obtained from the implementation of the use of traditional game tools for the development of P5 at Kapanewon Girisubo Kindergarten.This type of qualitative research uses interview, observation, and documentation techniques. This research explored how the utilization traditional game tools are used to development of the Pancasila student profile project at Kapanewon Girisubo Kindergarten. The analysis used is the Miles and Huberman model. Researchers reduced, presented, drew conclusions, and verified data.Based on the results of the data analysis, the conclusions were obtained: (1) The learning planning of the utilization of traditional game tools for the development of P5 at kindergarten Kapanewon Girisubo the was very good, the school analysed of the characteristics of the educational unit, formulated program plan, defined, objectives and involved all school members. (2) The implementation of the use of traditional game tools for the development of P5 at Kapanewon Girisubo Kindergarten had been carried out well, using taditional games that have evoved, such as Javanese tradisional children'sgames (3) Evaluation of the use of traditional game tools for the development of P5 in Kapanewon Girisubo Kindergarten, Evaluation was good, which includes reflection on activities carried out after completing learning and to determine next steps. (4) The results obtained from the implementation of the use of tools Traditional games for the development P5 at Kapanewon Girisubo Kindergarden, were is good, that traditional game tools can enhance the profile dimensions of the Pancasila students profile.